Revised checklist of Australian butterflies (Lepidoptera: Hesperioidea and Papilionoidea): Addendum and Errata - Braby, Michael F. (Zootaxa, 2011)
In the published version of the Appendix ‘Revised checklist of Australian butterflies (Lepidoptera: Hesperioidea and Papilionoidea)’ (Braby, 2010 pp. 49-76) a number of typographical mistakes, omissions, nomenclatural inaccuracies and corrections to gender agreement among species group names have come to the author’s attention. These errors are corrected below.